The Role of Education in Productivity of Human Resources and Increasing Job Opportunities - Maryam Hayati; Hafizullah Aiuby (CV. AFDIFAL MAJU BERKAH, 2023)
In today٫s era, no organization able to survive without paying attention to the human force and its constructive role in providing services. In fact, the level of ability of organizations, companies and the criterion of getting a job is education and workforce productivity. The purpose of this research is to find out the place of education in the improvement and productivity of human resources and its effect on increasing job opportunities. This research was conducted using the library method and the sources used in this research are books, articles, figures and reports. The result of this research shows that employees work with 20 to 30 percent of their abilities before training, but when they are trained and properly motivated, they reveal 80 to 90 percent of their abilities and competencies and increases productivity. Increasing productivity increases the demand for Recruitment and increases job opportunities.